Enhancing crop water productivity and aquifer recharge in arid regions: Water balance insights for optimized hybrid irrigation in pecan orchards - Jorge L. Preciado; Alexander G. Fernald; Richard Heerema; Curt Pierce (Agricultural Water Management)
Converting to drip irrigation from flood irrigation promises to increase crop water productivity (WPC) but at the potential costs of lower crop yield and less deep percolation that could recharge aquifers. This study hypothesizes a significant difference in recharge rates in pecan orchards under flood and drip irrigation systems in the Mesilla Valley of southern New Mexico, USA, with differences in yield between the drip and the flood irrigation systems. For three years of measurements from 2019 to 2021, we found that of the total water applied, deep percolation rates were 11–52 % for the flood irrigated orchard and 4.4–4.8 % for the drip irrigated orchard, highlighting the greater efficiency of drip irrigation and greater deep percolation under flood irrigation. The results revealed that the drip irrigated orchard exhibited a higher WPC of 2.7 kg/mm, whereas the flood irrigated orchard yielded a WPC of 1.1 kg/mm during the study period. Even though the statistical analysis detected no significant differences in total in-shell weight or in-shell nut weight. These findings suggest that the observed differences between flood and drip irrigation systems do not translate to significant differences in total in-shell weight or in-shell nut weight. This study makes a significant contribution to existing literature by providing estimates and comparisons of deep percolation under different irrigation systems, using field data from pecan orchards. This research introduces a novel approach that optimizes the benefits of both irrigation systems. This hybrid approach has the potential to enhance water management practices in arid regions.